Spatial Assessment of Poverty Distribution in West Java Province (Global Scientific Review, 2023)
Poverty is a major issue in many countries around the world. This is a condition that individuals are unable to meet basic needs such as foods, clothings, medicines, and housings. Poverty alleviation becomes a primary goal of the national development programs in accordance with the mainstream agenda of the Millennium Development Goals (MDGs) and Sustainable Development Goals (SDGs) as stated in the National Long-Term Development Plan (RPJPN 2005-2025). The national poverty alleviation programs implemented by the government have successfully reduced the percentage of poverty, even though the nominal number of the poor people remains quite high. Development is essentially a continuous process encompassing various dimensions, including social, economic, and environmental dimensions aimed at the welfareness of the society. The measurement of the social and economic conditions of a population (poverty) is a part of the assessment of development success. A method to integrate poverty attribute data with maps allows us to visualize the distribution of poor populations in a region. The poverty data may be presented in two data models: macrolevel poverty data and micro-level poverty data. In order to achieve spatial equality, the visualization process is presented at the district/city level throughout the West Java Province. In addition, the process is developed under the WebGIS environment, making this poverty information easily accessible to users. Spatial assessment information on the distribution of poor populations and the success of poverty alleviation programs can be accessed through https://jabar.netlify.app/.